Methodological recommendations for conducting control work in mathematics teaching - Shivkant Tiwari; Dragan Obradovic; Laxmi Rathour; Lakshmi Narayan Mishra; Vishnu Narayan Mishra (The Journal of Engineering and Exact Sciences)
The importance of mathematics as a subject in building intellectually strong personalities, creating and nurturing work habits in students, training them for independent work, are undoubtedly important for acquiring permanent and active mathematical knowledge as a basis for studying mathematics at the next level of education. There is an undoubted need to improve the teaching practice, the current teaching, which only transfers knowledge to the degree of recognition and reproduction.